2012
DOI: 10.1136/bmjopen-2011-000641
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative cross-sectional study of the perceived causes of depression in South Asian origin women in Toronto: Table 1

Abstract: ObjectiveTo explore how South Asian origin women in Toronto, Canada, understand and explain the causes of their depression.DesignCross-sectional in-depth qualitative interviews.SettingOutpatient service in Toronto, Ontario.ParticipantsTen women with symptoms of depression aged between 22 and 65 years of age. Seven were from India, two from Sri Lanka and one from Pakistan. Four were Muslim, three Hindu and three Catholic. Two participants had university degrees, one a high school diploma and seven had completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
(46 reference statements)
2
30
1
Order By: Relevance
“…4245 In one Canadian study, a group of SA women with depression were interviewed to assess the explanatory models they used to understand their illness. 43 Participants largely felt that their depression was an outcome of personal, family, cultural, and social circumstances. 43 Stresses in familial relationships, aging, isolation, migration, stigma, economic difficulties, and discrimination were all cited as reasons for depression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4245 In one Canadian study, a group of SA women with depression were interviewed to assess the explanatory models they used to understand their illness. 43 Participants largely felt that their depression was an outcome of personal, family, cultural, and social circumstances. 43 Stresses in familial relationships, aging, isolation, migration, stigma, economic difficulties, and discrimination were all cited as reasons for depression.…”
Section: Resultsmentioning
confidence: 99%
“…43 Participants largely felt that their depression was an outcome of personal, family, cultural, and social circumstances. 43 Stresses in familial relationships, aging, isolation, migration, stigma, economic difficulties, and discrimination were all cited as reasons for depression. 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research in this area has consistently found that depressed patients of East Asian and South Asian cultural origin tend to emphasize somatic rather than psychological symptoms and favor interpersonal or contextual rather than biological explanations for their distress, as compared with their Western counterparts (Ekanayake et al, 2012; Karasz, 2005; Karasz et al, 2007; Kleinman, 1977; Yeung and Kam, 2005). Karasz has generalized this finding further to state that “non-Western, nonwhite, and non-middle-class individuals suffering from depression are more likely to exhibit somatic disturbances in medical settings than are Western middle class individuals” (Karasz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the interpretive process of a narrative gains its status of enunciation, particularly in what is being said in the interface of pain and psychological suffering. [13] The enunciation of the disease, therefore, arises from the communicative movement between what is said and what is interdict of childhood depression in family narratives. [14] In this context, the said assumes own verbalized sentence, in other words, the statement of the complaint.…”
Section: Introductionmentioning
confidence: 99%